Full mouth rehabilitation of young adults with oligodontia: Two case reports emphasizing implantology, prosthodontics, and restorative intervention - Chu, Seng Boon; Ooi, Huay Shuan (IIUM Journal of Orofacial and Health Sciences, 2023)
Oligodontia, a severe form of hypodontia characterized by the absence of multiple permanent teeth, presents considerable challenges in dental treatment. Successful management of this condition requires early detection and a comprehensive, multidisciplinary approach. While the complete restoration of missing teeth is typically postponed until all permanent teeth have erupted or after orthodontic therapy, it is crucial to consider additional factors such as the patient’s oral hygiene status, socioeconomic circumstances, and long-term maintenance therapy for achieving optimal treatment outcomes. This case reports showcase the effective treatment of oligodontia in two young male patients: a 17-year-old Chinese individual and a 19-year-old Caucasian individual. These cases serve to emphasize the significance of early diagnosis, multidisciplinary collaboration, and personalized treatment planning in addressing the challenges posed by oligodontia. Although orthodontic intervention was not pursued in the presented cases, it is important to recognize its integral role in the overall treatment of oligodontia. The restoration of missing dentition has a profound positive impact on aesthetics, function, and the overall quality of life. The presented cases underscore the importance of early intervention and sustained motivation throughout the treatment process. By emphasizing the value of early detection, comprehensive teamwork, and individualized treatment approaches, clinicians can strive to achieve optimal outcomes for patients with oligodontia.